Knowledge of Athlete Nutrition, Parents, and Macronutrients Intake of Karate Shindoka Athletes - Roziana, Roziana; Erowati, Dewi; Siregar, Fahma Rahmadani (JURNAL PROTEKSI KESEHATAN, 2023)
Athletes have a higher activity compared to ordinary people, so their nutritional needs are different and require specific attention with proper dietary arrangements to be able to meet their nutritional needs. Good nutritional knowledge is expected to influence the consumption of correct and appropriate foods so that athletes can meet their nutritional needs. It aims to support increased stamina so athletes can support their achievements well. This study aims to determine the level of nutritional knowledge of athletes, parents, and the macronutrient intake of karate athletes Shindoka Riau. The sampling technique was total sampling with 25 respondents aged 12-18. Data collection was using questionnaires and food recall 2x24 hours. The results showed that athletes were 88% less energy intake, 96% less carbohydrates, 88% less fat, and 68% less protein. The level of knowledge of athletes is less than 68%, and the level of knowledge of parents is sufficient, which is 52%. It concluded that most of the nutritional knowledge of athletes and their parents in the less category had nutrient intake in the less category.